A Smart Money: How Jargons Work as Persuasion Technique in Cryptocurrency Ecosystem: Smart Money: Bagaimana Jargon Berfungsi sebagai Teknik Persuasi dalam Ekosistem Cryptocurrency - Haris, Arkin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Cryptocurrency's hegemony as revolutionary breakthrough for the future financial transaction system prompts an examination of the role of jargon in persuasive techniques on social media platform X. The study aims to explore linguistics form of crypto jargon and recognize how jargon functions in persuasive techniques related to cryptocurrency on platform X. Focusing data on posts from crypto influencer @saylor and crypto exchange @binance, this study identifies 10 types of cryptocurrency jargon, highlighting the dominance of compounding. A new category, Visual Jargon is introduced, emphasizing visual elements like icons and logos, supported by GIF, image, and emoticon features on platform X. The study demonstrates the effectiveness of jargon in fostering group identity within the cryptocurrency ecosystem, as evidenced by survey results indicating over 90% agreement on its positive function as a symbol of membership and prestige. The hashtag feature on platform X facilitates connections among crypto enthusiasts. Semantically, connotative meaning of crypto jargon enables precise communication, reinforcing concept of identification within persuasive techniques. Grammatically, it introduces specific structures that accurately simplify communication. It aligns with the positive function of jargon in improving language efficiency, in accordance with the posting guidelines on platform X which are limited to only 280 characters. However, audience comments indicate potential lack of understandings among those outside crypto community.